(untitled) (ASEAN Engineering Journal, 2025)
Construction delay is one of the cost-related issues in the construction industry. Introducing Building Information Modelling (BIM) aided in the cost management of the construction project through early clash detection. Thus, BIM reduces the chances of construction delay and becomes a significant solution for cost issues in the construction industry. Therefore, this paper focuses on the cost management between the BIM and the non-BIM construction projects in Malaysia. The objectives of this paper are: (i) to study the issues of cost management and (ii) to analyse and compare the cost management between the BIM and non-BIM projects in the Malaysian construction industry. A qualitative method was adopted in this study. A semi-structured interview was conducted among the Grade 6 and 7 contractors involved in both BIM and non-BIM projects in Kuala Lumpur and Johor Bahru. The result revealed that the main cost-related issue the construction industry faces is the project's delay. With the implementation of the BIM, it contributes to the reduction of the actual cost by 10% - 30%. However, the implementation of BIM in Malaysia's construction industry is still in the infant stage, and it requires collaboration from the government sector to boost BIM implementation.